115k views
4 votes
What is the result of substituting for y in the bottom equation?

y = x + 3

y= x2 + 2x-4

A. x+ 3 = x2 + 2x - 4

B. X+ 3 = x2

C. y= (x+3)2 + 2(x + 3) - 4

D. y= x2 + 2x - 4 - (x+3)

User ComeIn
by
5.8k points

1 Answer

7 votes

Answer:

(A)
x + 3= x^2 + 2x-4

Explanation:

Given the equations:


y = x + 3\\y= x^2 + 2x-4

Substitution simply means replacing the variable y in the second equation with its equivalent x+3 from the first equation.

Substitution of y into
y=x^2 + 2x-4 gives us:


x + 3= x^2 + 2x-4

The correct option is A.

User Delimited
by
6.1k points